My Place in the Sun : Life in the Golden Age of Hollywood and Washington - Stevens, George, Jr., 1932- (Book collections on Project MUSE., 2022)
"The son of a celebrated Hollywood director emerges from his father's shadow to claim his own place as a major force in American culture. George Stevens, Jr. tells an intimate and moving tale of his relationship with his Oscar-winning father and his own exciting career in Hollywood and Washington. Fascinating people, priceless stories and a behind-the-scenes view of some of America's major cultural and political events grace this riveting memoir. George Stevens, Jr. grew up in Hollywood working on film classics with his father and writes vividly of his experience on the sets of A Place in the Sun (1951), Shane (1953), Giant (1956) and The Diary of Anne Frank (1958). He explores how the magnitude of his father's talent and achievements left him with questions about his own abilities and future. The younger Stevens began to forge his unique career when the legendary broadcaster Edward R. Murrow recruited him to work at the United States Information Agency in John F. Kennedy's Washington. He began his service in government by initiating what has been called the Golden Age of USIA filmmaking. In 1967 he became the founding director of the American Film Institute, placing him at the leading edge of culture and politics, shepherding the rescue of thousands of endangered motion pictures, and training a new generation of filmmakers. He created the Kennedy Center Honors and began making distinguished films and television programs that celebrated American culture and explored social justice. He earned an Oscar and other accolades, including fifteen Emmys, two Peabody Awards, and the Humanitas Prize. Stevens provides a fascinating look at a pioneering American family that spans five generations in the performing arts, from the San Francisco stage in the 19th century to Academy Award-winning films, Emmy Award-winning television programs and a Broadway play. He shows us the private side of the dazzling array of people who cross his path, including Elizabeth Taylor, Sidney Poitier, Robert and Ethel Kennedy, Yo-Yo Ma, Cary Grant, James Dean, Bruce Springsteen, Barack and Michelle Obama, and many more. In My Place in the Sun, George Stevens, Jr. shares his lifelong passion for film and commitment to the performing arts. He provides an insightful look at Hollywood's Golden Age and an insider's account of life in Washington as he collaborated with presidents, power brokers, media moguls and social activists. This magnificent and delightful memoir brings to life a sparkling era of American history and culture"--